POSITIONING INDONESIA IN THE INTERNATIONAL WORLD THROUGH ENERGY TRANSFORMATION - V.L. Sinta Herindrasti (Universitas Nasional, 2022)
Renewable energy (solar energy, wind, ocean, geothermal, bio-energy) is believed to be a “game-changer” in energy relations between countries and completely change the landscape of international relations. Fossil energy – which will soon become extinct – will inevitably be replaced by renewable energy and this energy transition will be an interesting phenomenon from a global geopolitical perspective. Fossil energy-producing countries, especially coal, oil, and natural gas, will be displaced by renewable energy-producing countries where the accompanying characteristics will change established patterns of strategy and cooperation. As a vast archipelagic country with enormous renewable energy potential, Indonesia – along with other major powers such as the United States, Europe, Russia, China, Japan, India, and OPEC countries – should be able to undertake utilization and mitigation strategies in this major transition. The emergence of the global energy game that will lead to a renewable energy regime is a big momentum that will shape the future of energy geopolitics. Is Indonesia in the right direction and strategy in the context of this energy transition? How can Indonesia's energy strategy and policies position Indonesia internationally and make it a